2020
DOI: 10.1002/ppul.25167
|View full text |Cite
|
Sign up to set email alerts
|

Flexible through rigid bronchoscopy for airway foreign body: A good marriage of convenience!

Abstract: To the Editor, Aspiration of a foreign body is commonly reported among children. Considered the gold standard for extraction of airway foreign bodies, rigid bronchoscopy fails in up to7% 1,2 of cases. Although there are reports of successful use of flexible bronchoscope for airway foreign body removal it has many limitations. We describe an adolescent patient wherein a distally placed airway foreign body, after the failure of removal with rigid bronchoscope twice, could be removed successfully using flexible-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…19,21,36 Singal et al described how a flexible bronchoscope was inserted through a rigid scope to remove a foreign body from the airway of a 12-year-old girl. 58 These studies underline the need for specific tools to improve how flexible bronchoscopy is used to remove foreign bodies from children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,21,36 Singal et al described how a flexible bronchoscope was inserted through a rigid scope to remove a foreign body from the airway of a 12-year-old girl. 58 These studies underline the need for specific tools to improve how flexible bronchoscopy is used to remove foreign bodies from children.…”
Section: Discussionmentioning
confidence: 99%
“…In 29 of the 2588 cases a rigid endoscope was used to remove a foreign body out of the oropharynx after it had been extracted from the tracheobronchial tree with a flexible bronchoscope 19,21,36 . Singal et al described how a flexible bronchoscope was inserted through a rigid scope to remove a foreign body from the airway of a 12‐year‐old girl 58 …”
Section: Discussionmentioning
confidence: 99%
“…As the choice of anesthesia and mode of ventilation (spontaneous versus controlled) during bronchoscopic removal of AFBs are currently debated, the efficacy of newer sedatives such as fospropofol, remifentanil, and dexmedetomidine during bronchoscopy are being evaluated 12,13 . Additionally, new surgical techniques for removal of AFBs such as endoscope‐assisted rigid bronchoscopy, flexible bronchoscopy, flexible bronchoscopy through a rigid bronchoscope, and flexible bronchoscopy aided with a suction tube are being developed and studied 14–17 …”
Section: Discussionmentioning
confidence: 99%
“…12,13 Additionally, new surgical techniques for removal of AFBs such as endoscope-assisted rigid bronchoscopy, flexible bronchoscopy, flexible bronchoscopy through a rigid bronchoscope, and flexible bronchoscopy aided with a suction tube are being developed and studied. [14][15][16][17] Although NSQIP-P reports data in a large number of categories, this study is limited by the variables not reported in the database. It would have been useful to collect data on anesthetic techniques to determine their impact on adverse events.…”
Section: Discussionmentioning
confidence: 99%